2020
DOI: 10.3390/life10120357
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Regulates Cardiac Energy Metabolism in Sedentary and Trained Mice

Abstract: The role of canonical Wnt signaling in metabolic regulation and development of physiological cardiac hypertrophy remains largely unknown. To explore the function of β-catenin in the regulation of cardiac metabolism and physiological cardiac hypertrophy development, we used mice heterozygous for cardiac-specific β-catenin knockout that were subjected to a swimming training model. β-Catenin haploinsufficient mice subjected to endurance training displayed a decreased β-catenin transcriptional activity, attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…25,26 After birth, βcatenin promotes the hypertrophic growth of cardiomyocytes. 27,28 Its signaling activity decreases during heart maturation and remains low in the healthy adult heart, but it is still essential for maintaining heart function. [28][29][30] The reactivation of WNT/β-catenin pathway occurs in response to pathological stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 After birth, βcatenin promotes the hypertrophic growth of cardiomyocytes. 27,28 Its signaling activity decreases during heart maturation and remains low in the healthy adult heart, but it is still essential for maintaining heart function. [28][29][30] The reactivation of WNT/β-catenin pathway occurs in response to pathological stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…β-catenin was able to transfer into the nucleus to affect the expression of hypertrophy-related genes [ 46 ]. When β-catenin haplo-insufficient mice were subjected to endurance training, the cardiomyocytes’ hypertrophic growth was attenuated [ 47 ]. This suggests that inhibition of β-catenin could decrease cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…In unstimulated cells, non-phosphorylated cytoplasmic β-catenin translocated/ accumulated within the nucleus to enable downstream gene regulatory activity (26,27). Recently, a series of investigations indicated that the activation of the Wnt/β-catenin signaling pathway contributes to liver injury induced by alcohol consumption (13), and its downregulation increased the levels of proteins involved in glucose aerobic metabolism and β-oxidation in a mouse swimming training model (28). The above data demonstrate that the Wnt/β-catenin signaling pathway plays an important role in inflammation and metabolism, though the involvement of Wnt/β-catenin signaling in lipid metabolism and the inflammatory response of the liver remains uncertain.…”
Section: Discussionmentioning
confidence: 99%